PRODUKSI DAN NILAI NUTRISI HIJAUAN PUERARIA PHASEOLOIDES DENGAN INOKULASI MIKORIZA VESIKULAR- ARBUSKULAR DAN PEMUPUKAN P - Dwi Retno Lukiwati; Robert Jonggi Maruli Simanungkalit (JURNAL LITBANG PROVINSI JAWA TENGAH, 2003)
Vesicular-arbuscular mycorrhizae (VAM) inoculation of forage crops in combination with P. fertilization are important to improve forage crops production and nutritive value in the nonproductive soils. A greenhouse experiment was carried out to study the effect of YAM (Glomusfasciculatum, Entrophosphoracolumbiana, and Gfasciculatum+E. columbiana) in combination with P fertilization (superphosphate-36 and rock phosphate) on the dry matter production, N and Zn uptake of Pueraria phaseoloides (puero), Factorial 2x4 in completely randomized design was used in 5 replicates. The results showed that dry matier production, N and Zn uptake of puero with YAM inoculation were significantly higher compared to without YAM inoculation. Dry matter production, N and Zn uptake of puero with superphosphate-36 were signifcantly higher compared to rock phosphate fertilization.